2019
DOI: 10.1073/pnas.1916892116
|View full text |Cite
|
Sign up to set email alerts
|

The iron deficiency response in Arabidopsis thaliana requires the phosphorylated transcription factor URI

Abstract: Iron is an essential nutrient for plants, but excess iron is toxic due to its catalytic role in the formation of hydroxyl radicals. Thus, iron uptake is highly regulated and induced only under iron deficiency. The mechanisms of iron uptake in roots are well characterized, but less is known about how plants perceive iron deficiency. We show that a basic helix-loop-helix (bHLH) transcription factor Upstream Regulator of IRT1 (URI) acts as an essential part of the iron deficiency signaling pathway in Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 49 publications
1
131
2
Order By: Relevance
“…A latest study found that AtFIT promotes the nuclear accumulation of AtbHLH39, an Arabidopsis homolog of OsIRO2, in Arabidopsis (Trofimov et al, 2019). Similarly, Arabidopsis bHLH IVc TFs promote the nuclear accumulation of AtbHLH121 which is required for the maintenance of Arabidopsis Fe homeostasis (Kim et al, 2019; Gao et al, 2020; Lei et al, 2020). Although we did not observe the localization change of OsIRO2 in response to Fe deficiency in our transient expression assays, the increased nuclear accumulation of OsIRO2 under Fe deficiency condition was observed by Wang et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A latest study found that AtFIT promotes the nuclear accumulation of AtbHLH39, an Arabidopsis homolog of OsIRO2, in Arabidopsis (Trofimov et al, 2019). Similarly, Arabidopsis bHLH IVc TFs promote the nuclear accumulation of AtbHLH121 which is required for the maintenance of Arabidopsis Fe homeostasis (Kim et al, 2019; Gao et al, 2020; Lei et al, 2020). Although we did not observe the localization change of OsIRO2 in response to Fe deficiency in our transient expression assays, the increased nuclear accumulation of OsIRO2 under Fe deficiency condition was observed by Wang et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A short time ago, another piece was added to the iron deficiency response puzzle [68]. Upstream Regulator of IRT1 (URI), basic helix-loop-helix transcription factor, appears to have a central role as an iron-dependent switch.…”
Section: Ups In the Regulation Of Iron Homeostasismentioning
confidence: 99%
“…These four members regulate the expression of FER-LIKE IRON-DEFICIENCY-INDUCED TRANSCRIPTION FACTOR ( FIT ), bHLH Ib genes ( bHLH38 , bHLH39 , bHLH100 , and bHLH101 ) and POPEYE ( PYE ) (Zhang et al 2015; Li et al 2016; Liang et al 2017). Recently, three studies characterized the functions of bHLH121 (Kim et al 2019; Gao et al 2020; Lei et al 2020), and Lei et al (2020) found that bHLH121 is also directly regulated by bHLH IVc. FIT interacts with bHLH Ib TFs and they synergistically promote the expression of Fe-uptake associated genes IRT1 and FRO2 (Yuan et al 2008; Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…bHLH105/ILR3 also functions as a negative regulator when it interacts with PYE (Tissot et al 2019). In contrast, bHLH121 is required for activation of numerous Fe deficiency responsive genes (Kim et al 2019; Gao et al 2020; Lei et al 2020). Moreover, both bHLH 121 and PYE interact with bHLH IVc to regulate Fe homeostasis in Arabidopisis (Long et al 2010; Selote et al 2015; Kim et al 2019; Tissot et al 2019; Gao et al 2020; Lei et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation